# solve using a graphing calculator log(base 4)(x+2)-log(base 5)(x-1)=1 e^2x=x+2

*print*Print*list*Cite

Expert Answers

embizze | Certified Educator

Solve `log_4(x+2)-log_5(x-1)=1` :

We can rewrite using the change of base formula: `log_ba=(ln(a))/(ln(b))`

`(ln(x+2))/(ln(4))-(ln(x-1))/(ln(5))=1`

Now we can graph and look for the intersection:

**Using the intersect feature we find the solution to be x=2.**

**This is easily verifiable: `(ln(4))/(ln(4))-(ln(1))/(ln(5))=1-0=1` as required.**

(2) Solve `e^(2x)=x+2`

Again we can graph both functions and find the intersection:

The intersect feature gives `x~~.44754216,y~~2.4475422` and `x~~-1.980974,y~~.01902602`